TGFβ/TNFα-Mediated Epithelial-Mesenchymal Transition Generates Breast Cancer Stem Cells with a Claudin-Low Phenotype - Asiedu, Michael K. (2011)
Breast cancer recurrence is believed to be caused by a sub-population of cancer cells that possess the stem cell attribute of treatment resistance. Recently, we and others have reported the generation of breast cancer stem cells (BCSCs) by epithelial to mesenchymal transition (EMT), although the physiological process by which these cells may arise in vivo remains unclear. We show here that exposure of tumor cells to TGFβ and TNFα induces EMT and, more importantly, generates cells with a stable BCSC phenotype which is demonstrated by increased self-renewing capacity, greatly increased tumorigenicity, and increased resistance to oxaliplatin, etoposide and paclitaxel. Furthermore, gene expression analyses found that the TGFβ/TNFα-derived BCSCs showed down regulated expression of genes encoding Claudin 3, 4 and 7 and the luminal marker, cytokeratin 18. These changes indicate a shift to the claudin low molecular subtype, a recently identified breast cancer subtype characterized by the expression of mesenchymal and stem cell-associated markers and correlated with a poor prognosis. Taken together, the data show that cytokine exposure can be used to generate stable BCSCs ex vivo, and suggest that these cells may provide a valuable tool in the identification of stem cell-directed biomarkers and therapies in breast cancer.